Silicone adhesive multilayer foam dressings as adjuvant prophylactic therapy to prevent hospital‐acquired pressure ulcers: a pragmatic noncommercial multicentre randomized open‐label parallel‐group medical device trial. (28th December 2020) - Beeckman, D.; Fourie, A.; Raepsaet, C.; Van Damme, N.; Manderlier, B.; De Meyer, D.; Beele, H.; Smet, S.; Demarré, L.; Vossaert, R.; de Graaf, A.; Verhaeghe, L.; et al.
Summary: Background: Silicone adhesive multilayer foam dressings are used as adjuvant therapy to prevent hospital‐acquired pressure ulcers (PUs). Objectives: To determine whether silicone foam dressings in addition to standard prevention reduce the incidence of PUs of category 2 or worse compared with standard prevention alone. Methods: This was a multicentre, randomized controlled medical device trial conducted in eight Belgian hospitals. At‐risk adult patients were centrally randomized ( n = 1633) to study groups based on a 1 : 1 : 1 allocation: experimental groups 1 ( n = 542) and 2 ( n = 545) – pooled as the treatment group – and the control group ( n = 546). The experimental groups received PU prevention according to hospital protocol, and a silicone foam dressing on the relevant body sites. The control group received standard of care. The primary endpoint was the incidence of a new PU of category 2 or worse at the studied body sites. Results: In the intention‐to‐treat population ( n = 1605), PUs of category 2 or worse occurred in 4·0% of patients in the treatment group and 6·3% in the control group [relative risk (RR) 0·64, 95% confidence interval (CI) 0·41–0·99, P = 0·04]. Sacral PUs were observed in 2·8% and 4·8% of the patients in the treatment group and the control group, respectively (RR 0·59, 95% CI 0·35–0·98, P = 0·04). Heel PUs occurred in 1·4% and 1·9% of patients in the treatment and control groups, respectively (RR 0·76, 95% CI 0·34–1·68, P = 0·49). Conclusions: Silicone foam dressings reduce the incidence of PUs of category 2 or worse in hospitalized at‐risk patients when used in addition to standard of care. The results show a decrease for the sacrum, but no statistical difference for the heel and trochanter areas. Abstract : What is already known about this topic? The incidence of hospital‐acquired pressure ulcers (PUs) remains high despite the implementation of best‐practice recommendations. The concept of using silicone foam dressings as an additional prophylactic strategy in PU prevention has been investigated in previous studies but with some limitations. Most RCTs were monocentric studies, restricted to either critically ill or acute care patients and did not observe more than two anatomical at‐risk skin sites, which limited the generalizability of the findings. What does this study add? This large pragmatic RCT suggests that it is beneficial to use silicone adhesive multilayer foam dressings on the sacrum, in addition to standard of care, to help prevent hospital‐acquired PUs. Clinical decision making for heel dressings should be based on the clinical effectiveness of the intervention weighed against the potential risk of falling. Linked Comment: F. Coyer. Br J Dermatol 2021; 185 :4–5 .